Avaliação de projetos de restauração de ecossistemas florestais - Guimarães, Lucas Ribeiro (2021)
The restoration of degraded areas is of paramount importance in restoring the dynamics, functioning and sustainability of ecosystems. In addition to the implementation of techniques for the restoration of flora, another fundamental step is the monitoring of restoration. In monitoring, the assessment of the recovery plan is carried out using performance indicators that are measured and quantified to verify the effectiveness of the restorative actions and whether the project is achieving its objective within the established deadline. Given this context, the present study aims to evaluate the restoration process in six fragments in different stages of restoration on the campus of the Federal University of Lavras (UFLA), through the use of performance indicators. Three of these areas were restored 5 years ago, while the other three are 10 years old after the implementation of the project. Studies were carried out on the floristic aspects, the structural and functional ecological processes of the vegetation, and physical analyzes of the soil through verifiers that allow to infer whether the ecosystem under restoration can be considered self-organized and functional, based on the ecology of the restoration. For the floristic analysis, the arboreal and regenerating strata were surveyed, evaluating the frequency, density, dominance and importance value index of the species to be surveyed, as well as the diversity, equability, similarity and leaf area indexes. Altogether, in the arboreal stratum, 511 individuals were surveyed, distributed in 49 species belonging to 28 families. In the regenerating stratum, 820 individuals were registered, distributed in 58 species belonging to the 31 families. In general, the species that obtained the highest importance value indexes were Citharexylum myrianthum, Guazuma ulmifolia and Schinus terebinthifolia, with a predominance of pioneer species in all strata. As expected, the five-year-old areas had lower performances in the analyzed parameters, when compared to the more advanced areas. However, it can be concluded that the results found are in accordance with previous studies carried out on the campus UFLA, and that the analyzed parameters have proved to be effective, indicating that the restoration project has been achieving its objective.